(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
This paper considers the commercial and altruistic nature of surrogacy in the light of the offence principle, analysing the legal interests protected by the Italian absolute prohibition of surrogacy, as laid down by the law on medically assisted procreation no. 40/2004. It starts by examining the exploitation of the surrogate mothers on the basis of the prohibition of financial gain provided for in Article 21 of the Oviedo Convention and it then deals with the position of the unborn, in order to investigate the consequences for it. The conclusion is a rebuttal of the logic of the gift: when adopting a child-prospective, all forms and arrangements of surrogacy are called into question. Moreover, the Author argues for the need of an international regulation on the practice, which must take into account the best interest of the child as a third and external party in such conducts, without having to take second place to the intended parents’ reproductive destre.